ПРОГНОСТИЧНЕ ЗНАЧЕННЯ ПУХЛИНОІНФІЛЬТРУЮЧИХ ЛІМФОЦИТІВ ТА ЇХ ЗВ’ЯЗОК З КЛІНІКОМОРФОЛОГІЧНИМИ ХАРАКТЕРИСТИКАМИ АДЕНОКАРЦИНОМИ ТОВСТОЇ КИШКИ - SHKURUPII, B.; ZAKHARTSEVA, L. (PH Akademperiodyka, 2024)
Aim. To study the prognostic value of the density of tumor-infiltrating lymphocytes (TILs) and its association with other clinical-morphological parameters in colon adenocarcinomas (CAC). Materials and Methods. 236 CAC samples were examined. TILs density was estimated as the percentage of tumor stromal area occupied by TILs. By the index of TILs density, the patients were divided into 3 groups: TILs 0—9% (n = 88); TILs 10—39% (n = 106); TILs > 40% (n = 42). Dependent on this index, their overall survival (OS) was analyzed. Results. Kaplan — Meier curves revealed a significant (p < 0.001) difference in the OS for patients with different TILs infiltration intensities. Multivariate Cox’s proportional hazard regression model analysis has confirmed that patients with moderate TILs density (HR 0.57, 95% CI 0.34—0.96, p = 0.035) had better OS rates compared to low TILs density. TILs were associated with the stage (p < 0.001), lymph node metastasis pN (p < 0.001), distant metastasis M (p < 0.001), and the patient’s outcome (p < 0.001). Conclusion. TILs can be considered an additional prognostic tool during regular histological examination and are strongly associated with the most significant clinical-morphological features of CAC.